Good Corporate Governance on Stock Prices of Companies Listed in the KOMPAS 100 Index 2014-2018 - Christian, Jiwana; Juanda, Bambang; Bandono, Bayu (Universitas Prasetiya Mulya, 2020)
This research aimed to analyze the effect of good corporate governance on stock prices. It was conducted on companies listed on the Indonesia Stock Exchange which were included in the KOMPAS100 Index in 2014-2018 by using a purposive sampling technique. Data analysis used was a panel data regression method with a fixed-effect model - least square dummy variable. The results of the study show that the number of board of the commissioner meetings, return on assets, earnings per share, and price to book value had significant effects on stock prices in a positive direction; the number of directors, education/training for corporate secretaries, and price to earnings ratio had positive but insignificant effects; the number of independent commissioners and the number of board of the director meetings had negative but insignificant effects on share prices. The novelty in this study was the addition of the variable of company secretary as an indicator of corporate governance, which was not found in previous studies. Besides, this study added a dummy interaction to see the effect of the level of corporate compliance on corporate governance.